2011
DOI: 10.21977/d97110003
|View full text |Cite
|
Sign up to set email alerts
|

Arts-Infused Learning in Middle Level Classrooms

Abstract: Inequities in arts education permeate the educational landscape. Some schools provide programs for a few students; others provide for all students, but only sporadically (Burton, Horowitz, & Abeles, 1999; Fowler, 1996). According to a Los Angeles County Art Commission (2001) study, wealthy and high-achieving students are more likely to receive arts education than low-performing and economically-disadvantaged students. Sadly, arts education is virtually nonexistent for marginalized youth. "Disadvantaged and at-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Several studies reviewed in this study reported gains in student self-efficacy and self-esteem (Jacobs 2005;Lorimer 2011;Bassett 2010;Prager 2006;Ponder and Kissinger 2009;Smith and McKnight 2009;Durham 2010). Zimmerman (2000) reported that self-efficacy beliefs are sensitive to subtle changes in students' performance context.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Several studies reviewed in this study reported gains in student self-efficacy and self-esteem (Jacobs 2005;Lorimer 2011;Bassett 2010;Prager 2006;Ponder and Kissinger 2009;Smith and McKnight 2009;Durham 2010). Zimmerman (2000) reported that self-efficacy beliefs are sensitive to subtle changes in students' performance context.…”
Section: Discussionmentioning
confidence: 78%
“…This was a recommendation made in the CEC evidence-based practice manual for when a researcher finds studies that meet a mix of group, single-subject, and/or correlational criteria (Council for Exceptional Children 2008). Under these guidelines, multi-arts integration was found to be a practice with positive effects for disadvantaged populations' reading achievement and potentially positive effects for math achievement, creativity/critical thinking, self-efficacy, motivation, cooperation, and student engagement (Lorimer 2011;Scriven 2008;Prager 2006;Smith and McKnight 2009;Yorke-Viney 2007;Ingram and Riedel 2003;Nelson 2007;Brouillette et al 2008;Catterall and Waldorf 1999). Therefore, it can cautiously be regarded as an evidence-based practice to increase reading achievement based on this one evaluation of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, the reality is such that the theory of flow has been rarely used in public education to date and there is still little research on flow in FL education. The conducted literature review has shown that flow has been studied in the educational contexts of a few developed countries, such as the U.S.A., Japan, Denmark, and Finland (Andersen, 2005;Lorimer, 2015;Nakamura & Csikszentmihályi, 2014;Shernoff & Csikszentmihalyi, 2009). No applications of flow theory in education have been found in developing countries, including Russia, which became the context of this study.…”
Section: Problem Statementmentioning
confidence: 99%
“…The existence of numerous researches which indicate that creative arts develop class participation, as well as the creative and critical thinking skills of the children, obliges the utilization of artistic activities and products within language education (Gormley & McDermott, 2016). The key purpose within education is to enhance the production and informational organization of the student; rather than focusing on multiple choice tasks, education provided through literature is particularly effective in this regard (Lorimer, 2011). Personal features such as trust, creative thinking, motivation, effective participation, team work and empathy can all be developed through art-based teaching methods, and through these methods students can be provided with the skills they need to express themselves more accurately (Barton & Baguley, 2014).…”
Section: Introductionmentioning
confidence: 99%